NOVEL MUTATIONS IN THE NON-STRUCTURE PROTEIN 2 OF SARS-CoV-2 - Mohsen Nakhaei; Zohreh-Al-Sadat Ghoreshi; Mohammad Rezaei Zadeh Rukerd; Hedyeh Askarpour; Nasir (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Mutation in the genome of SARS-CoV-2 may play a role in immune evasion, pathogenicity and speed of its transmission. Our investigation aimed to evaluate the mutations that exist in the nsp2.